Making Treatment Decisions for Oneself: Weighing the Value - Brock, Dan W. (The Hastings Center report, 2014)
Competent adults should be permitted to determine the course of their own lives. We may try to influence them. We may ask them, perhaps even implore them, to change their minds. But in the end, they are in charge of their lives. They get to choose their careers, whether and whom to marry, whether to exercise, and whether to have surgery. This emphasis on respect for patients’ autonomy may seem to imply that allowing patients to make their own decisions should always take precedence over other considerations. Given this presumption, there has been almost no discussion in the medical literature or elsewhere about how important this value is and whether it should sometimes be balanced against and give way to other values. This absence of guidance is especially problematic in cases where respect for patient autonomy conflicts with promoting patients’ clinical interests.